Electoral incentives to coalition formation in multiparty presidential systems. (November 2021) - Borges, André; Turgeon, Mathieu; Albala, Adrián
Coalition theories of presidential regimes have frequently assumed that coalition formation is a mostly post-electoral phenomenon. We challenge this view by showing that pre-electoral bargaining shapes to a substantial extent minority presidents' disposition to cooperate with the legislature by forming a majority cabinet. Examining a dataset of pre- and post-electoral coalitions from 18 Latin American countries, we find that majority coalition cabinets are more likely to occur when elected presidents form pre-electoral coalitions (PECs), to the extent that pre-electoral agreements create stronger incentives for cooperation, by relying on a broader set of rewards than any post-electoral agreement. Moreover, we find that the likelihood of majority coalition formation increases as the share of PEC seats increases, thus reducing the need to engage in post-electoral bargaining. Our findings carry important implications for the study of cabinet formation in presidential regimes by introducing pre-electoral agreements as a key determinant of cabinet formation.